COVID-19 and the mental health of frontline healthcare workers in Nigeria - Aguh, Johanna I.; Adamu, VE (Orapuh Journal, 2021)
Introduction Not many events can cause a standstill in economic and social life worldwide, but the world is facing one of the most unexpected events in the form of a deadly pandemic. COVID-19 has become a severe global health threat since its emergence. Purpose The study aimed to assess the effects of COVID-19 on the mental health of frontline healthcare workers in Nigeria. Materials & methods 10 journal and 4 newspaper publications were used as study materials for this review. Search engines used were Google Scholar, ProQuest, Cochrane Library, PubMed, and EMBASE. We used Libraries to confirm if someone else has done a systematic review of the topic. Results This review confirmed that there was more psychological stress due to COVID-19 on the frontline and non-frontline healthcare workers than the general population in Nigeria. More studies showed that frontline healthcare workers have increased mental stress because of the direct contact they have with COVID-19 patients, and inadequate infrastructure and hospital supplies (PPE). Conclusions There need to be more studies on the mental health of Nigerian healthcare workers. The Nigerian Government needs to be more involved with improving mental health through health policies such as signing the mental health bill and creating a Mental Health Department in the Ministry of Health.